Effects of discrimination by sex and race on the early careers of British medical graduates during 1981-7. Issue 6758 (27th October 1990) - McKeigue, P M; Richards, J D; Richards, P
Abstract : OBJECTIVE--To examine the possible effects of discrimination by sex and race on the career patterns of doctors up to six years after qualifying. DESIGN--Postal questionnaire follow up survey. PARTICIPANTS--1572 Doctors who graduated from five British medical schools in 1981, 1983, and 1985, including 587 women and 131 doctors from ethnic minorities. MAIN OUTCOME MEASURES--Reported success rates of applications for training posts. RESULTS--Comparison of the career patterns of women and men yielded no evidence of discrimination against women in competition for posts. In contrast, there were striking differences in career patterns between graduates of native European origin and those of ethnic minority origin. Graduates from ethnic minorities reported lower success rates and more difficulty in obtaining house officer posts, registrar posts, and places in vocational training schemes in general practice. Most of this discrimination seemed to occur at the stage of shortlisting for interview. Graduates from ethnic minorities were more likely than graduates of native European origin to have experienced spells of unemployment while seeking work. They were also more likely to have changed their original choice of career because of difficulty in obtaining suitable training posts or unfavourable career prospects. CONCLUSIONS--Discrimination against ethnic minorities occurs in the competition for training posts among graduates from British medical schools. There was no evidence of discrimination against women graduates. Shortlisting procedures based on objective scoring systems may help to ensure equality of opportunity in future.